2001
DOI: 10.1016/s1010-7940(01)00621-2
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation after coronary artery bypass grafting: does the type of procedure influence the early postoperative incidence?

Abstract: (1) Atrial fibrillation is a common postoperative complication after myocardial revascularization procedures which prolongs ICU stay. (2) The study did not show that the incidence of postoperative AF is influenced by the technique of coronary artery bypass grafting: with or without CPB. (3) The prevalence of postoperative AF increase when CABG is combined with valve replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
36
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 16 publications
4
36
1
2
Order By: Relevance
“…This is consistent with our previously published findings based on a smaller number of patients [18]. Recently, Bohatch Junior et al [19] demonstrated no significant difference in the incidence of postoperative AF between on-pump and off-pump patients.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with our previously published findings based on a smaller number of patients [18]. Recently, Bohatch Junior et al [19] demonstrated no significant difference in the incidence of postoperative AF between on-pump and off-pump patients.…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, this is the first report demon- strating an increased risk of new-onset POAF after CABG surgery in patients with fQRS. Atrial fibrillation is a relatively frequent complication of cardiac surgery, occurring in approximately 25%-40% of patients following CABG (15)(16)(17). In our study, POAF occurred in 22.8% of patients who had undergone isolated CABG surgery.…”
Section: Discussionmentioning
confidence: 99%
“…9 The use of cardiopulmonary bypass, the type of cardioplegia, presence of myocardial ischemia, and number of grafts placed are all possible factors responsible for the occurrence of postoperative AF. 10 It has been proposed that endogenous adenosine, released due to tissue hypoxia, may cause early (< 48 h) postoperative AF. 5 Cox observed that atrial ischemia following cardiac surgery could induce early AF.…”
Section: Discussionmentioning
confidence: 99%